A parametric study of friction stir welded AA6061/SiC AMC and its effect on microstructure and mechanical properties. (2021) - Kumar, Devender; Ottarackal, Denny J.; Acharya, Uttam; Medhi, Tanmoy; Saha Roy, Barnik; Saha, Subhash Chandra
Abstract: The present study investigates the effect of parametric variations on microstructural and mechanical properties of friction stir welded (FSW) 6 mm thick as-cast AA6061/SiC Aluminum Matrix Composite (AMC) joints. The study has been designed by varying the traverse speed, tool rotational speed and tilt angle up to various levels. Microstructural investigations of welded samples were performed using low-resolution Light Optical Microscopy (LOM) and Scanning Electron Microscopy (SEM). Energy-dispersive X-ray spectroscopy (EDS) is conducted to analyze the chemical composition and reinforcement distribution. To see the effect of parametric variation on mechanical property of the joint, ultimate tensile strength (UTS), percentage (%) elongation and hardness are investigated to support the study. As the optimum parametric values were somewhere missing in context to FSW of AMCs therefore present study deals with carefully deriving optimum weld parameters contributing to both sound weld as well as mechanical properties of the welded specimen. Tool tilt angle played a major role in determining the UTS of the welded specimen besides the tool rotational speed and welding speed making it one of the critical parameter for deciding mechanical properties of the welded specimen.